2019
DOI: 10.5114/dr.2019.92736
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of fractional laser

Abstract: The action of fractional lasers is based on the principle of fractional photothermolysis, which consists in generating in the skin a mesh of microthermal treatment zones surrounded by healthy, undamaged tissue. The most important factors determining the effectiveness of the procedure and the risk of developing adverse effects are: depth, size and density of microthermal treatment zones. The laser beam energy set by the operator is responsible for the depth of microthermal treatment zones penetration into the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 38 publications
(180 reference statements)
0
14
0
Order By: Relevance
“…Graber showed that in a group of 422 patients, 35% of individuals prophylactically treated for HSV still developed the infection. This study concluded that premedication with acyclovir, valacyclovir, or famciclovir for 1 to 2 days before the procedure is advised only for those with a history of HSV 9 . Furthermore, Al‐Niaimi 16 suggests that the risk of scarring is so high in cases of HSV that empiric prophylactic medication is the norm.…”
Section: Infectionmentioning
confidence: 97%
See 4 more Smart Citations
“…Graber showed that in a group of 422 patients, 35% of individuals prophylactically treated for HSV still developed the infection. This study concluded that premedication with acyclovir, valacyclovir, or famciclovir for 1 to 2 days before the procedure is advised only for those with a history of HSV 9 . Furthermore, Al‐Niaimi 16 suggests that the risk of scarring is so high in cases of HSV that empiric prophylactic medication is the norm.…”
Section: Infectionmentioning
confidence: 97%
“…Fungal infections mostly involve Candida albicans . According to Szczepanik‐Kułak, this can be prevented by giving patients at greatest risk fluconazole 100 mg four times per day for 5 days 9 …”
Section: Infectionmentioning
confidence: 99%
See 3 more Smart Citations